2015
DOI: 10.1080/10286632.2015.1027698
|View full text |Cite
|
Sign up to set email alerts
|

The participation myth

Abstract: Policy rhetoric around strategies to and the value of increasing participation in the arts has been well documented internationally over more than a decade. But in the UK, which is the focus for this article, targets to increase participation have been consistently missed and there remains a direct correlation between those taking part in cultural activity and their socio-economic status.The starting point for this article is to examine the barriers to increasing participation in the arts and question the way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 17 publications
0
40
0
6
Order By: Relevance
“…The decisions from these third parties can influence the exchanges in the arts in different ways, because they can be variously reliable, contingent upon these assessors' (past) involvement in the arts (Trimarchi 2003). The efficacy of third-party assessment systems has been questioned, as they embroil human behavior that could be tainted by subjective biases, professional prejudices, self-interest, resistance to change, and ideology (Bertelli et al 2014;Jancovich 2017;Lewandowska 2017). Worst-case scenario, "given the relevance of their evaluations for the determination of the economic value of art products, collusion between agents and critics/experts can occur, strengthening agents' contractual power against principals, and introducing a further bias in the outcome of such complex exchanges" (Trimarchi 2003, 375).…”
Section: Agency Theory: Goal Heterogeneity and Information Asymmetry mentioning
confidence: 99%
See 1 more Smart Citation
“…The decisions from these third parties can influence the exchanges in the arts in different ways, because they can be variously reliable, contingent upon these assessors' (past) involvement in the arts (Trimarchi 2003). The efficacy of third-party assessment systems has been questioned, as they embroil human behavior that could be tainted by subjective biases, professional prejudices, self-interest, resistance to change, and ideology (Bertelli et al 2014;Jancovich 2017;Lewandowska 2017). Worst-case scenario, "given the relevance of their evaluations for the determination of the economic value of art products, collusion between agents and critics/experts can occur, strengthening agents' contractual power against principals, and introducing a further bias in the outcome of such complex exchanges" (Trimarchi 2003, 375).…”
Section: Agency Theory: Goal Heterogeneity and Information Asymmetry mentioning
confidence: 99%
“…For example, while scholars observe that, in particular settings, the decision-making processes on subsidizing the arts still appear to "easily become enmeshed with political perspectives" (Shin and Kim 2018, 99), it is equally found that the installment of third-party assessments mitigates the "association between political factors and funding decisions" (Bertelli et al 2014, 342). Also, while it is evidenced that a narrow range of voices from a powerful cultural elite still put their mark on decision making in the arts (Jancovich 2017), it is equally demonstrated that the privileged positions in those assessments appear to have shifted from experts who possess the capacity of aesthetic judgment to "those who can claim technical expertise" in political (evidence-based) decision making (Lewandowska 2017, 11). All in all, subsidy allocation by involving third parties is found to be characterized by "symbolic mechanisms of power" between assessors and the government (D'Andrea 2017, 247) and leading to "unanticipated outcomes and inconsistencies between rhetoric and conduct" (Zan et al 2012, 76).…”
Section: Introductionmentioning
confidence: 99%
“…O'Brien, Laurison, Miles, & Friedman, 2016). Nevertheless, the debate over cultural consumption continues to focus largely on issues of improving access to traditional arts forms as unique repositories of cultural value (Crossick & Kaszynska, 2016;DCMS, 2016;Jancovich, 2015).…”
Section: Policy and Theorymentioning
confidence: 99%
“…They were inscribed in its original Charter and retained in subsequent renewals. The 'issue' of limited participation in subsidised culture, however, remains 'unsolved' (Jancovich 2015;Stevenson 2015). As a result, non-audiences, which are seen as 'disengaged', 'excluded', 'inactive', 'disenfranchised', and so become targets of policy intervention to address the assumed deficiencies of their cultural consumption, in what is obviously a deficit model of policy making (Miles & Sullivan 2010).…”
Section: On Making An Impact: Getting the Cultural Sector To Listenmentioning
confidence: 99%